Design and Synthesis of Restoring Technique Based Dual Mode Floating Point Divider for Fast Computing Applications - Salman Faraz, Shaikh; Suryawanshi, Yogesh; Kakde, Sandeep; Tijare, Ankita; Thakare, Rajesh (International Journal of Engineering and Technology, 2018)
Floating point division plays a vital role in quick processing applications. A division is one amongst the complicated modules needed in processors. Area, delay and power consumption are the main factors that play a significant role once planning a floating point dual-precision divider. Compared to different floating-point arithmetic, the design of division is way a lot of sophisticated and needs longer time. Floating point division is that the main arithmetic unit that is employed within the design of the many processors in the field of DSP, math processors and plenty of different applications. This paper relies on the dual-mode practicality of floating point division. The proposed designed architecture supports the single precision (32-bit) as well as double precision (64-bit) IEEE 754 floating point format. It uses restoring division technique for the fraction part division. This design consists of varied sub-modules like shifters, exceptional handlers, Normalizers and many more.Â Â